K.U. INGARD, Notes on Sound Absorption Technology, Noise Control Foundation, Poughkeepsie - ENGEL, Zbigniew (Archives of Acoustics, 1996)
We obtained new book "Notes on Sound Absorption Technology". This book has been written by Professor K.U. Ingard. Professor K. Uno Ingard was educated at the Chalmers University of Technology in Gothenburg, Sweden and at the Massachusetts Institute of Technology in Cambridge, Massachusetts, USA.